Diagnosing coronary artery disease after a positive coronary computed tomography angiography: the Dan-NICAD open label, parallel, head to head, randomized controlled diagnostic accuracy trial of cardiovascular magnetic resonance and myocardial perfusion scintigraphy. (13th February 2018) - Nissen, L; Winther, S; Westra, J; Ejlersen, J A; Isaksen, C; Rossi, A; Holm, N R; Urbonaviciene, G; Gormsen, L C; Madsen, L H; Christiansen, E H; Maeng, M; et al.
Abstract: Aims: Perfusion scans after coronary computed tomography angiography (CCTA) in patients with suspected coronary artery disease (CAD) may reduce unnecessary invasive coronary angiographies (ICAs). However, the diagnostic accuracy of perfusion scans after primary CCTA is unknown. The aim of this study was to determine the diagnostic accuracy of cardiac magnetic resonance (CMR) and myocardial perfusion scintigraphy (MPS) against ICA with fractional flow reserve (FFR) in patients suspected of CAD by CCTA. Methods and results: Included were consecutive patients (1675) referred to CCTA with symptoms of CAD and low/intermediate risk profile. Patients with suspected CAD based on CCTA were randomized 1:1 to CMR or MPS followed by ICA with FFR. Obstructive CAD was defined as FFR ≤ 0.80 or > 90% diameter stenosis by visual assessment. After initial CCTA, 392 patients (23%) were randomized; 197 to CMR and 195 to MPS. Perfusion scans and ICA were completed in 292 patients (CMR 148, MPS 144). Based on the ICA, 117/292 (40%) patients were classified with CAD. Sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) for CMR were 41%, 95% CI [28–54], 84% [75–91], 62% [45–78], and 68% [58–76], respectively. For the MPS group 36% [24–50], 94% [87–98], 81% [61–93], and 68% [59–76], respectively. Conclusion: Patients with low/intermediate CAD risk and a positive CCTA scan represent a challenge to perfusion techniques indicated by the low sensitivity of both CMR and MPS with FFR as a reference. The mechanisms underlying this discrepancy need further investigation.